INVENTARISASI SPESIES MANGROVE DI KAWASAN PESISIR DESA JENILU KABUPATEN BELU NUSA TENGGARA TIMUR - Emilia Juliyanti Bria (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2023)
Mangroves are important ecosystems in coastal areas that have a major influence on the survival of the biota in them. This study aims to inventory the existence of mangrove species in the coastal area of Jenilu Village, Kakuluk Mesak District, Belu Regency, East Nusa Tenggara. The method used is the observation method. Data obtained by means of inventory and identification of mangrove species. The results showed that there were 2 mangrove species from the Rhizophoraceae Family, Order Malpighiales, namely Rhizophora apiculata Blum and Rhizophora mucronata Poir. These two species are distinguished based on the characters on their morphological characteristics. The data from this research can become the basic data for species development and subsequent conservation efforts.